2015
DOI: 10.1021/acs.jpcb.5b03081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymethylene Spacer of Cationic Gemini Surfactants on Solvation Dynamics and Rotational Relaxation of Coumarin 153 in Aqueous Micelles

Abstract: The present work demonstrates the solvation dynamics and rotational relaxation of Coumarin 153 (C-153) in the micelles of a series of cationic gemini surfactants, 12-s-12, 2Br(-) containing a hydrophobic polymethylene spacer with s = 3, 4, 6, 8, 12. Steady-state and time-correlated single-photon counting (TCSPC) fluorescence spectroscopic techniques have been used to carry out this study. Steady-state and TCSPC fluorescence data suggest that C-153 molecules are located at the Stern layer of micelles. While pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 80 publications
(221 reference statements)
7
62
1
Order By: Relevance
“…It depicts that C-480 is present neither at the core of the micelles nor in the bulk water, but somewhere in between these two. According to literature reports, the micropolarity of the Stern layer is similar to methanol, 50 , 51 , 53 , 69 , 70 on the basis of which we state that C-480 molecules are mostly residing in the Stern layer. It is pertinent to note that C-480 being present in the Stern layer of micelles, microenvironment remains more or less same with the addition of urea in micellar systems.…”
Section: Resultssupporting
confidence: 60%
“…It depicts that C-480 is present neither at the core of the micelles nor in the bulk water, but somewhere in between these two. According to literature reports, the micropolarity of the Stern layer is similar to methanol, 50 , 51 , 53 , 69 , 70 on the basis of which we state that C-480 molecules are mostly residing in the Stern layer. It is pertinent to note that C-480 being present in the Stern layer of micelles, microenvironment remains more or less same with the addition of urea in micellar systems.…”
Section: Resultssupporting
confidence: 60%
“…Larger values around 4 nm are reported for 12-s-12 aggregates which may have resulted from the selection of a SANS data fitting model different to the usual core-shell prolate spheroidal model [37]. The 12-s-12 micellar diameters resulting from fluorescence anisotropy measurements give substantially smaller values from 0.86 to 1.23 nm [26].…”
Section: Aggregation In Aqueous Solutionmentioning
confidence: 93%
“…In the field of nonionic systems, they interact with cyclodextrins [22] and nonionic triblock copolymers [23,24] and form mixed micelles with single-chain nonionic surfactants [25]. The bisammonium gemini molecules with the polymethylene spacer have been found to be an efficient solvation tool for electronically excitable molecules [26]. The investigations of the aggregation properties at the air-water interface showed that the area per gemini surfactant molecule gives the maximum value at the spacer length of 12 CH 2 groups which is interpreted in terms of diminishing spacer rigidity and increased flexibility with the increasing spacer length [27].…”
Section: Introductionmentioning
confidence: 99%
“…also have reported that gemini surfactants with small spacer chain form bigger micelles . We have reported earlier the diameter of the micelle of each of pure 12–3‐12, 12–6‐12 and 12–12‐12 as 1.24 nm, 1.01 nm and 0.86 nm, respectively . At higher concentration of surfactants (data given in Table ), sizes of small particles observed are in these ranges only.…”
Section: Resultsmentioning
confidence: 93%
“…Zana et al have reported, and we have also seen in one of our earlier studies, that the microviscosity of gemini micelles increases with decreasing polymethylene spacer chain length. Thus the above mentioned trend in fluorescence intensity could be due to increasing microviscosity of micelles with decreasing spacer chain length.…”
Section: Resultsmentioning
confidence: 99%